'We are all alike': Composite Portraits, CONVICTS, and the Ethics of Representation. - Shaw, Kim (Australian Historical Studies, 2025)
In the digital age, historians face a transformation in methodologies due to vast data availability. While quantitative techniques are considered essential for managing large datasets, their increased use demands heightened vigilance. Through a critique of the CONVICTS exhibition, viewed at the Hobart Penitentiary Chapel in 2019, this article illustrates why it is important to have a clear understanding of the purpose and limitations of the methodologies we engage. CONVICTS remakes Francis Galton's 'pictorial statistics', using contemporary methods to create composite portraits of nineteenth and twenty-first-century convicts. While Galton sought to identify the defining features of the 'ideal criminal', the creators of CONVICTS draw attention to the commonality and likeness of these portraits to our experience of the average person. However, presenting averaged faces as familiar and relatable can inadvertently reinforce biased judgments based on appearances. Moreover, the process of averaging faces erases individuality and fails to represent any actual convict.